2018
DOI: 10.3390/f9070375
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Alternative Thinning Operations in Mediterranean Softwood Plantations

Abstract: Abstract:Mediterranean pines account for 14,000 ha in Tuscany alone, where they form large and homogeneous stands and represent an important resource for the forest economy. Among the harvesting systems applied to thinning operations, the most popular are whole-tree and cut-to-length harvestings. Both systems can be deployed with different levels of mechanization. The decision about which system might be the best option in a specific case possibly leads to conflicts due to different management goals, for insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The final weights are the points of each criterion divided by the sum of all points. The selection of utility functions, preference functions and thresholds for this study was based on previous studies [44,80], as well as the authors' judgment. In MAUT method we used linear utility-function for all criteria while for PROMETHEE method, a V-shape preference function has been applied.…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The final weights are the points of each criterion divided by the sum of all points. The selection of utility functions, preference functions and thresholds for this study was based on previous studies [44,80], as well as the authors' judgment. In MAUT method we used linear utility-function for all criteria while for PROMETHEE method, a V-shape preference function has been applied.…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
“…In MAUT method we used linear utility-function for all criteria while for PROMETHEE method, a V-shape preference function has been applied. The preference threshold (for V-shape preference function) was set to be 10% of the highest value for each SI [44].…”
Section: Multi-criteria Decision Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the articles reporting sustainable analysis considered production costs (fixed and variable), total amount of wood harvested, time consumption, delays, gross domestic product, gross and local value added, trade, yearly net revenues of forest subjects, and fuel consumption [e.g., 8,16,40,74,90,91]. Cost and productivity can vary largely between countries and different scenarios related to different logging systems and assortments [21,22,41].…”
Section: Economic Impacts Of Forest Operationsmentioning
confidence: 99%
“…Consequently, improvements related to mechanized wood harvesting provided knowledge of information regarding the productivity and costs of a particular machine and/ or system, i.e., the reliability of these two pieces of information is fundamental for a better understanding of the productive system. Thus, it can be observed that the mechanization of the wood harvesting activity goes through major inno vations and technological advances (Simões et al 2014, Di Fulvio et al 2017, Kaakkurivaara and Kaakkurivaara 2018, but for this to occur, it is important to under-stand the processes, stages and work involved in this segment (Lindroos et al 2017, Schweier et al 2018, Blagojevic et al 2019, Kizha et al 2020, as well as factors involved in assessing forest planning (Mousavi et al 2011, Bodaghi et al 2018, Holzleitner et al 2018, Santos et al 2019. Although changes are often observed, culminating in the evolution of forest operations, differences in machine production costs may occur due to machine models or wood harvesting methods applied.…”
Section: Introductionmentioning
confidence: 99%